Population and Distribution Plant Pattern Paliasa (Kleinhovia hospita L.) in Bontobahari District - Wahyuni, Andi Sri; Prasetyo, Lilik Budi; Zuhud, Ervizal A. M. (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Paliasa is known as a traditional medicinal herb used by the people of South Sulawesi. Knowledge of the paliasa uses evolved from sempirical experience by intergenerational inheritance. This study aims to estimate the population and distribution patterns of Paliasa (Kleinhovia hospita L.) in District Bontobahari. In this research, it is used square plots square with 100 m x 100 m zise and 18 plots in total. Paliasa distribution patterns are determined by record the coordinates of Paliasa in the plots using GPS (Global Positioning System). The results showed that the population of Paliasa in the Bontobahari District based on six types of land use reached 597 individuals and the distribution is clumped. Keywords: Bontobahari, paliasa, pattern of distribution